EARNINGS MANAGEMENT: FREE CASH FLOW, LEVERAGE, PROFITABILITY MODERATED BY FIRM SIZE - Ricardo Hadi Widjaja, Liana Susanto (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to determine the effect of free cash flow, leverage, and profitability on earnings management with firm size as a moderating variable on manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The research uses a sample of 71 companies each year. The method of analysis used is panel data regression analysis with E-views 9.0. The results of the research with a significance level of 5% shows that free cash flow and profitability have no effect on earnings management while leverage has a negative effect on earnings management. Firm size strengthen the effect of leverage on earnings management and firm size does not moderate the effect of profitability on earnings management.